Temporal Distance and Message Concreteness in Facebook Ads: The Moderating Effects of Social Distance. - Xue, Fei (2024)
The study examined the effects of social distance, temporal distance, and message concreteness on Facebook users’ response to News Feed advertising. A 2 (social distance: low vs. high) × 2 (temporal distance: near future vs. distant future) × 2 (message: abstract vs. concrete) between-group design was utilized to explore the main and interaction effects of three factors on Facebook users’ attitude-toward-the-ad, brand interest, and purchase intention. Results suggested that social distance via Facebook moderated the congruency between temporal distance and message concreteness. When the ads were affiliated with close friends, effects predicted by the Construal Level Theory (CLT) were found. The findings indicate the importance of social distance when examining temporal distance and message concreteness in a social media setting. Social media marketers should consider the strength of social relationships based on time of the event and advertising message formats. Future research could examine other products and services and utilize different research methods, such as eye-tracking or field studies. The study tested CLT in a social media setting, particularly the role of relationship strength among Facebook users. It adds theoretical value to existing CLT research and provides valuable insights for social media marketers. DOI: https://doi.org/10.54663/2182-9306.2024.v.12.n.22.33-53